Malawi Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Baseline Evaluation Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
As part of the US government's Feed the Future initiative that aims to address global hunger and food security issues in sub-Saharan Africa, the US Agency for International Development is supporting three multi-stakeholder agricultural research projects under Africa Research In Sustainable Intensification for the Next Generation (Africa RISING - AR) program. The overall aim of the program is to transform agricultural systems through sustainable intensification projects in Ghana, Tanzania, Malawi, Ethiopia and (potentially) Zambia. In Malawi, the project (led by IITA) will be supporting cereal-based Farming Systems. The International Food Policy Research Institute (IFPRI) leads the monitoring and evaluation (M&E) activities of the AR program. As part of the M&E activities in Malawi, IFPRI contracted Invest in Knowledge Initiative (IKI) to conduct baseline household and community surveys in Ntcheu and Dedza districts. Ntcheu and Dedza are the two districts in which participatory action r